Criminalistics classification of criminal offences in the field of economic activity - V. O. Usatii (Bulletin of Kharkiv National University of Internal Affairs)
The article determines that the group of criminal offences in the field of economic activity is numerous, and despite a number of common features, it is still quite diverse both in terms of the specifics of the object of the offence and the methods of commission, as well as other features. In addition, the study analyses the typical approaches of criminal law scholars to the classification of crimes in the field of economic activity.